2017
DOI: 10.1016/j.amjmed.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Nitrate Use and Risk of Hip Fracture

Abstract: Purpose Nitrates, commonly used anti-anginal medications, also have beneficial effect on bone remodeling and bone density, particularly with intermittent use. However, their effect on fracture risk is not clear. We examined the relation of short-acting nitrate use (proxy for intermittent use) to the risk of hip fracture in a large cohort of older adults with ischemic heart disease. Materials and Methods Participants ≥ 60 years old with ischemic heart disease and without history of hip fracture from The Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…The claims data study examined class of medications rather than specific medications, but reported similar findings for antidepressants; however, our study did not have sufficient numbers of users of medication categories to closely examine many medications. Although a previous study found nitrates to protect against hip fracture, we found use in the past 2 years increased the risk of hip fracture. This could be because of the disease for which they were prescribed (CVD) or because of the hypotensive effects of taking nitrates.…”
Section: Discussioncontrasting
confidence: 99%
“…The claims data study examined class of medications rather than specific medications, but reported similar findings for antidepressants; however, our study did not have sufficient numbers of users of medication categories to closely examine many medications. Although a previous study found nitrates to protect against hip fracture, we found use in the past 2 years increased the risk of hip fracture. This could be because of the disease for which they were prescribed (CVD) or because of the hypotensive effects of taking nitrates.…”
Section: Discussioncontrasting
confidence: 99%
“…After a period when research slowed, these studies, like the legendary phoenix, renew the exploration of NO in bone biology, and provide exciting translational potential. consistent with the generally negative outcomes from clinical nitrate trials for the prevention of bone loss (6,7). But these data might also suggest that NO has noncell-autonomous effects on other tissues that can regulate bone remodeling, thereby balancing potentially adverse cell-autonomous effects from the ASL-deficient state.…”
Section: How No Drives Bone Formationsupporting
confidence: 57%
“…Taken together, the strong in vitro evidence, the ease and previous widespread clinical use of NO-donor drugs, and promising observational data sustained a two-decade effort to establish organic nitrates as a preventive therapy for osteoporosis. But, the case-control, cohort, and clinical trials were either underpowered or were confounded by reverse causation (6,7). More importantly, the reports from the definitive NO trial, heralded in several editorials, showing strong beneficial effects of nitroglycerin on areal and volumetric bone mineral density, and a reduction in bone resorption, were ultimately retracted because of scientific fraud in 2011 and 2017 (8,9).…”
Section: The Exploration Of Nitric Oxide In Bone Biologymentioning
confidence: 99%
“…The incident hip fracture during a 1‐year follow‐up period was the primary outcome of the study. Hip fracture was identified by using Read Codes as previous studies have done in THIN …”
Section: Methodsmentioning
confidence: 99%